Factors Influencing Fashion Consciousness in Muslim Fashion Consumption among Zillennials - Ocktavia, Annisa Kartika; Marenza, Silvya Eka; Al-Ayubi, Solahuddin; Maulana, Huda Kurnia (Journal of Islamic Economic Laws, 2024)
This study aims to analyze the factors that influence awareness of Muslim fashion consumption among Generation Z in Indonesia. Data is collected using a questionnaire using the convenience sampling method. A total of 255 final data points can be used for data analysis using SmartPLS. The results show that the style of dressing, the motivation for fashion, the uniqueness of fashion, and the source of fashion knowledge positively influence fashion awareness and indirectly influence Muslim fashion consumption. The findings from this study provide valuable insights to stakeholders in the fashion industry, including designers, retailers, and entrepreneurs, in understanding Muslim market segments. Practitioners can develop Muslim fashion products that are sharia-friendly and effectively target Muslim consumer segments through appropriate marketing strategies.